Study about the effects of vitamins AD3E on the blood concentration of glucose, cholesterol and calcium on racehorses (Journal of Hama University, 2019)
The study was carried out in Damascus Countryside on (40) head horses race, including (20) head was used as a control group, and (20) head of horses given the group of vitamins AD3E (experiment). To study the effect of giving the group of vitamins AD3E on the blood concentration of glucose, cholesterol and calcium, after all horses were performed 1600 m race. Blood samples were collected from the jugular vein for all horses in both groups and at a sample rate per day during the two days before the race until the day after the race ended. The results of laboratory tests for serum samples showed a significant increase (p